The Self-Regulation and Self-Control Factors Affecting the Growth Mindset of Hospitality Industry Students and Personnel - Tadawattanawit, Surakiat; Kiatkamonmarn, Chayawat (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2023)
The purposes of this research were: 1) to study the growth mindset level of students and service industry personnel and 2) To study the factors of self-regulation and self-control affecting the growth mindset level of students and service industry personnel. The sample was students and personnel in the service industry, divided into 28 people in the service industry and 120 students in the service industry. The research tool used was a questionnaire. Data were analyzed using statistics including frequency, percentage, mean, standard deviation, and multiple regression analysis. The results are as follows: 1) Students and service industry personnel have the growth mindset and partially fixed mindset ( = 37.53, SD = 5.21). 2) Self-regulation and self-control influenced the growth mindset with a statistical significance level of 0.05. Self-control and self-regulation were able to explain 3.30 percent of the growth mindset level of students and service sector employees. (R2 = 0.033).